Influence of microporous layer on corrosion of metallic bipolar plates in fuel cells - Castanheira,L; Bedouet,M; Kucernak,A; Hinds,G (Journal of Power Sources, 2019)
The effect of the presence of a microporous layer on the propensity for corrosion of metallic bipolar plates in an operating polymer electrolyte membrane fuel cell is investigated using an in situ reference electrode array. The local potential at the surface of the cathode bipolar plate is significantly more negative in the presence of the microporous layer, which is attributed to the higher ionic resistance of the aqueous phase in the reactant transport layer associated with more effective removal of water from the catalyst layer/reactant transport layer interface. As a result the bipolar plate is effectively shielded from elevated potentials that may be present at the cathode electrode, even during start-up and shutdown of the cell. Revision of ex situ test protocols for candidate bipolar plate materials, surface treatments and coatings is recommended to reduce unnecessary conservatism in testing.